FRANCHISE GROWTH AND IMPACT IN OGAN KOMERING ULU - Harby R. Wiralaga (STIE DWI SAKTI BATURAJA, 2013)
This paper is to contrast the positive and negative impact of franchise in Ogan Komering Ulu, since modern retail franchises are hypothetically remark to hold responsible for overthrowing the existing local retails. The role of government, local and central, is also remark as the sole policy maker to halt and trim down any negative impacts, and to sustain and radiate positive impacts.